1990
DOI: 10.1016/0009-2541(90)90082-i
|View full text |Cite
|
Sign up to set email alerts
|

Effects of structural relaxation on cationic tracer diffusion in silicate melts

Abstract: Dingwell, D.B., 1990. Effects of structural relaxation on cationic tracer diffusion in silicate melts. Chem. Geol., 82:209-216.The glass transition in silicate melts is a curve in time-temperature space marking the transition of the melt structure from an unrelaxed, disequilibrium glass to a relaxed, equilibrium liquid. Tracer diffusivity data obtained in glasses vs. liquids cannot be compared without consideration of the effects of this transition. For tracer diffusivity experiments, two time scales are impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 34 publications
4
33
0
Order By: Relevance
“…E Ca does, however, appear to be strongly correlated with the ratio D Ca / D Si (Fig. 4), which represents the ratio of the diffusivity of a "solute" component relative to that of the "solvent" The observed range in D i /D Si and its explanation have been described previously (Dingwell, 1990) and it has been shown that D i /D Si generally increases with increasing liquid viscosity g (cf. Dingwell, 2006).…”
Section: Isotope Separation By Diffusion In Silicate Meltsmentioning
confidence: 82%
“…E Ca does, however, appear to be strongly correlated with the ratio D Ca / D Si (Fig. 4), which represents the ratio of the diffusivity of a "solute" component relative to that of the "solvent" The observed range in D i /D Si and its explanation have been described previously (Dingwell, 1990) and it has been shown that D i /D Si generally increases with increasing liquid viscosity g (cf. Dingwell, 2006).…”
Section: Isotope Separation By Diffusion In Silicate Meltsmentioning
confidence: 82%
“…The B tracer diffusivity is expected to be faster than, but perhaps within a log unit, of the Si tracer diffusivity at the same composition at the high temperatures of these experiments ( DINGWELL, 1990). The tracer di&sivity of Si in a melt may be related to the viscosity of the melt by the Eyring equation ( GLASSTONE et al, 194 I ) and calculations for a wide variety of melts using reasonable estimates of jump distances (see, for example, SNIMIZU and KUSHIRO, 1984;DINGWELL, 1990) show the relationship to be a useful approximation. The jump distances used in these studies are the diameter of the oxygen ion (2.8 nm).…”
Section: Tracer Diffusivity Of Boronmentioning
confidence: 99%
“…For silicate melts the ot relaxation appears to be the Si-O bond exchange that occurs as silicon is exchanged among silicate species. High-temperature nuclear magnetic resonance (NMR) data Stebbins, 1990, 1994 Dingwell [1990] for Na20-3SIO2 melt, the rate of the faster [3 relaxation associated with the motion of alkalies in this melt can be related to the time required for tracer diffusion, electrical modulus relaxation, electrical conductivity relaxation, and lowtemperature (mechanical) internal friction relaxation. If the Si-O bond exchange structural relaxation occurring in a silicate melt does cause the observed relaxation of volume, shear, and enthalpy and contributes at the same rate to the equilibration of each of these properties, then the relaxation times and the rate-dependent glass transition temperatures determined for these three physical properties will be the same.…”
mentioning
confidence: 99%